Mouse LYVE-1 is an endocytic receptor for hyaluronan in lymphatic endothelium - Prevo, R; Banerji, S; Ferguson, D J; Clasper, S; Jackson, D G (The Journal of biological chemistry, 2001)
The glycosaminoglycan hyaluronan is a key substrate for cell migration in tissues during inflammation, wound healing, and neoplasia. Unlike other matrix components, hyaluronan (HA) is turned over rapidly, yet most degradation occurs not locally but within distant lymph nodes, through mechanisms that are not yet understood. While it is not clear which receptors are involved in binding and uptake of hyaluronan within the lymphatics, one likely candidate is the lymphatic endothelial hyaluronan receptor LYVE-1 recently described in our laboratory (Banerji, S., Ni, J., Wang, S., Clasper, S., Su, J., Tammi, R., Jones, M., and Jackson, D.G. (1999) J. Cell Biol. 144, 789-801). Here we present evidence that LYVE-1 is involved in the uptake of hyaluronan by lymphatic endothelial cells using a new murine LYVE-1 orthologue identified from the EST data base. We show that mouse LYVE-1 both binds and internalizes hyaluronan in transfected 293T fibroblasts in vitro and demonstrate using immunoelectron microscopy that it is distributed equally among the luminal and abluminal surfaces of lymphatic vessels in vivo. In addition, we show by means of specific antisera that expression of mouse LYVE-1 remains restricted to the lymphatics in homozygous knockout mice lacking a functional gene for CD44, the closest homologue of LYVE-1 and the only other Link superfamily HA receptor known to date. Together these results suggest a role for LYVE-1 in the transport of HA from tissue to lymph and imply that further novel hyaluronan receptors must exist that can compensate for the loss of CD44 function.